The elements of thinking in archipelago's fable from the perspective of children in the 21st century - Nik Muhamad Affendi, Nik Rafidah; Awang Pawi, Awang Azman; Hamdan, Rahimah (American Scientific Publishers, 2018)
The collections of fables and folklores from the archipelago in the 19th century have not been fully explored and studied extensively yet. This research discovered a number of selected collections of folklores in the library of Leiden University, Netherlands. One of the collections were these books, discovered in three versions; Tjarito-Tjarito Senderan Pengadjaran Kepada Manosia (1867) compiled by someone unnamed and Tjerita-Tjerita Peroepama-an compiled by Tweede Druk. Both books were printed in Batavia. Meanwhile, the third version of the manuscript entitled Tjarita-tjarita paroepamaan was handwritten in an exercise book by St. Malintang, a teacher at Paya Kumbuh, dated 20 December 1894. The stories in this special collection were presented in short forms with particular messages, suitable for children. This study seeks to classify and analyse the suitability of thinking elements contained in the stories from the perspective of children in the 21st century. A total number of 450 children in Malaysia were invited at random to see how they perceive the thinking in the mentioned folklore collection. The finding shows that the children enjoy reading stories related to their psychological development because the stories reinforce the elements of self-esteem and love and affection.